2019
DOI: 10.12911/22998993/105359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Longwave UV-B Radiation on Soybean Plants Grown at Increased Nickel Concentration in Soil

Abstract: Plants of soybean (Glycine max L.) cv. Augusta grew in the soil with addition of Ni in the concentration of 80 (C-80) or 120 mg•kg -1 dry mass (C-120) or without Ni (C-0), and they were subjected to UV-B (300 nm -315 nm) dose of 1.8 kJ m -2 d -1 for 28 days. The addition of nickel into soil in the concentration of 120 mg kg -1 (C-120) caused a decrease of the plant height by 35% compared to the control (C-0), and in the presence of UV-B (U-120) -by 43%. The shoot fresh and dry mass in the C-80 and C-120 plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Usually, UV-B exposure negatively affects plant growth, developmental processes, and morphology (Zuk-Golaszewska et al, 2003;Cechin et al, 2007;Salama et al, 2011;Chaudhary, Agrawal, 2015;Dotto, Casati, 2017). For example, it was found that the total dry weight of four cucumber cultivars (Krizek et al, 1997), the fresh and dry weight of soybean plants (Zhang et al, 2014;Skórska et al, 2019), and aerial dry mass of lettuce (Tsormpatsidis et al, 2008) were significantly decreased by UV-B in field attenuation studies. An apparent disparity in growth parameters was observed among rice varieties after exposure to UV-B (Hidema, Kumagai, 2006;Faseela, Puthur, 2019).…”
Section: Biomass Accumulationmentioning
confidence: 99%
“…Usually, UV-B exposure negatively affects plant growth, developmental processes, and morphology (Zuk-Golaszewska et al, 2003;Cechin et al, 2007;Salama et al, 2011;Chaudhary, Agrawal, 2015;Dotto, Casati, 2017). For example, it was found that the total dry weight of four cucumber cultivars (Krizek et al, 1997), the fresh and dry weight of soybean plants (Zhang et al, 2014;Skórska et al, 2019), and aerial dry mass of lettuce (Tsormpatsidis et al, 2008) were significantly decreased by UV-B in field attenuation studies. An apparent disparity in growth parameters was observed among rice varieties after exposure to UV-B (Hidema, Kumagai, 2006;Faseela, Puthur, 2019).…”
Section: Biomass Accumulationmentioning
confidence: 99%